2021
DOI: 10.3906/sag-2012-5
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of inflammatory arthritis patients for biological disease-modifying antirheumatic drugs in the first 100 days of the COVID-19 pandemic

Abstract: Background/aim To evaluate treatment adherence and predictors of drug discontinuation among patients with inflammatory arthritis receiving bDMARDs within the first 100 days after the announcement of the COVID-19 pandemic. Materials and methods A total of 1871 patients recorded in TReasure registry for whom advanced therapy was prescribed for rheumatoid arthritis (RA) or spondyloarthritis (SpA) within the 3 months (6–9 months for rituximab) before the declaration of COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The main reason for discontinuation was fear of the side effects of biological treatment. 14 This reason is in line with our (abovementioned) hypothesis of non-adherent behavior during the first SARS-CoV-2 lockdown.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The main reason for discontinuation was fear of the side effects of biological treatment. 14 This reason is in line with our (abovementioned) hypothesis of non-adherent behavior during the first SARS-CoV-2 lockdown.…”
Section: Discussionsupporting
confidence: 85%
“…Expected discordant proportions were based on the results of a previous study and expert opinion. 14 Characteristics of the study population and adherence measurements were described with means, standard deviations, medians, interquartile ranges, and percentages as appropriate. The internal reliability of the MARS-5 was calculated using Cronbach’s α.…”
Section: Methodsmentioning
confidence: 99%
“…Another Latin American study revealed that 90% (n = 293) of patients did not modify their drug schedule [16]. In various studies conducted in Italy, America, Spain and Turkey, it was reported that approximately 75-80% of patients did not change their treatment [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies were from Europe [15,16,18,19,21,22,24,[28][29][30][31]37,39,41,42,46,47], three from Africa [14,17,34], ten from North America [23,[25][26][27]33,35,36,38,45,48,49] and five from Asia [20,32,40,43,44]. Details of the included studies are shown in Table 1.…”
Section: Studies Originmentioning
confidence: 99%
“…The drugs mostly changed or stopped were bDMARDs and JAKi [28,32]. Low-dose prednisolone and csDMARDs were the least likely medications to be stopped.…”
Section: (C) Drugs Changed or Stoppedmentioning
confidence: 99%